THE CULTURE OF PHILOSOPHISING AND TEACHING - Мысык, И. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article is examined the specific character of philosophizing as unity of theoretical reflection and naive forms of cognitive activity, which reflect the vital ambiance of the subject of formation (education).